The Powell Hypothesis: Race and non-capital sentences for murder in Kentucky, 1976–1991 - Vito, Gennaro F. (American journal of criminal justice, 2000)
The 1987 U.S. Supreme Court decision McCleskey v. Kemp ruled, in part, that the findings of the Baldus study, offered by the petitioner to support a claim of racial bias in death penalty cases, were insufficient to demonstrate unconstitutional discrimination under the Fourteenth Amendment. Justice Lewis Powell offered additional justification for the ruling when he wrote, “If we accepted McCleskey’s claim that racial bias has impermissibly tainted the capital sentencing decision, we could soon be faced with similar claims as to other types of penalty. ” This statement has become labeled as the “Powell Hypothesis. ” This paper tests the “Powell Hypothesis” to determine whether race has an impact on sentences levied in noncapital murder cases in Kentucky between 1976 and 1991. The results indicate racial factors influenced sentence length in these cases.